Arabic Language Immersion-Based Learning Design for Teachers in Primary Islamic Schools - Rahmawati, Fitra Awalia; Subakir, Fairuz; Musthofa, Tulus; Zaini, Hisyam (Ijaz Arabi Journal of Arabic Learning, 2025)
Language learning should focus more on communicative orientation. However, in practice, the teaching of Arabic in Indonesia faces numerous challenges, particularly in the learning process, which often does not align with the goals and expectations of teachers. This study aims to describe the design of Arabic language instruction based on language immersion for teachers at the Madrasah Ibtidaiyyah level, addressing aspects such as competence, strategy, and assessment in teaching. This research employs a literature review approach, examining documents related to language immersion models as a reference for designing the ideal competencies, strategies, and evaluations for Arabic language learning in Madrasah Ibtidaiyyah. Data analysis in this study uses the Miles and Huberman model, which includes the following steps: data collection, data reduction, data display, and conclusion drawing and verification. The design of Arabic language instruction at the Madrasah Ibtidaiyyah level requires the coordination of multiple parties, such as teachers, in planning the lessons and the school in supporting processes and activities related to Arabic language learning. Arabic instruction at the Madrasah Ibtidaiyyah level can be carried out inside and outside the classroom, drawing on experiences and examples of activities from Islamic boarding schools (pesantren) that can be implemented at the Madrasah Ibtidaiyyah level. Furthermore, the learning of Arabic in schools for students at the Madrasah Ibtidaiyyah level should resemble how they learn their mother tongue at home.